International Joint Conference CISIS<U+0019>12-ICEUTEþ12-SOCOþ12 Special Sessions - Herrero, ℓlvaro.; Snàel, Vc̀lav.; Abraham, Ajith.; Zelinka, Ivan.; Baruque, Bruno.; Quintiǹ, Hčtor.; Calvo, Jos ̌Luis.; Sedano, Javier.; Corchado, Emilio. (Advances in Intelligent Systems and Computing, 2013)
This volume of Advances in Intelligent and Soft Computing contains accepted papers presented at CISIS 2012 and ICEUTE 2012, both conferences held in the beautiful and historic city of Ostrava (Czech Republic), in September 2012. CISIS aims to offer a meeting opportunity for academic and industry-related researchers belonging to the various, vast communities of Computational Intelligence, Information Security, and Data Mining. The need for intelligent, flexible behaviour by large, complex systems, especially in mission-critical domains, is intended to be the catalyst and the aggregation stimulus for the overall event. After a through peer-review process, the CISIS 2012 International Program Committee selected 30 papers which are published in these conference proceedings achieving an acceptance rate of 40%. In the case of ICEUTE 2012, the International Program Committee selected 4 papers which are published in these conference proceedings. The selection of papers was extremely rigorous in order to maintain the high quality of the conference and we would like to thank the members of the Program Committees for their hard work in the reviewing process. This is a crucial process to the creation of a high standard conference and the CISIS and ICEUTE conferences would not exist without their help.